2016
DOI: 10.1159/000445996
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Mammary Nutrigenomics and Changes in the Milk Composition due to Rapeseed or Sunflower Oil Supplementation of High-Forage or High-Concentrate Diets

Abstract: Background: Fatty acid (FA) composition plays a crucial role in milk nutritional quality. Despite the known nutritional regulation of ruminant milk composition, the overall mammary mechanisms underlying this regulation are far from being understood. The aim of our study was to determine nutritional regulation of mammary transcriptomes in relation to the cow milk composition. Methods: Twelve cows received diets differing in the forage-to-concentrate ratio [high forage (HF) and low forage (LF)] supplemented or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
1
19
1
Order By: Relevance
“…Moreover, COS and MAP decreased mRNA abundance of INSIG1 in both species, by 53 and 41%, respectively, in cows and by 30 and 37%, respectively, in goats. These results are not consistent with previous data (Leroux et al, 2016) that reported no variation in INSIG1 in cows fed a high forage supplemented with whole intact rapeseeds supplements; however, no variation of milk fat yield was observed in that study. In goats, the decrease of mRNA abundance of INSIG1 fed COS and MAP is in accordance with the reported decrease of INSIG1 mRNA in ovines (Carreño et al, 2016) fed diets supplemented with fish oil, which induced a decrease of 22% in milk fat yield.…”
Section: Mammary Metabolismcontrasting
confidence: 99%
“…Moreover, COS and MAP decreased mRNA abundance of INSIG1 in both species, by 53 and 41%, respectively, in cows and by 30 and 37%, respectively, in goats. These results are not consistent with previous data (Leroux et al, 2016) that reported no variation in INSIG1 in cows fed a high forage supplemented with whole intact rapeseeds supplements; however, no variation of milk fat yield was observed in that study. In goats, the decrease of mRNA abundance of INSIG1 fed COS and MAP is in accordance with the reported decrease of INSIG1 mRNA in ovines (Carreño et al, 2016) fed diets supplemented with fish oil, which induced a decrease of 22% in milk fat yield.…”
Section: Mammary Metabolismcontrasting
confidence: 99%
“…All mammary biopsies, which were the only chirurgical act, were performed with relevant national legislation and were done by an accredited person (N° of certification: 63–20). All collected samples have been previously described [ 13 , 46 ]. The present study was designed to identify miRNAs whose expression in the cow mammary gland is modulated by sunflower oil supplementation using a high throughput technology.…”
Section: Methodsmentioning
confidence: 99%
“…The sunflower oil was mixed and distributed with the forage. The effect of the sunflower oil supplementation on milk product and composition were previously described [ 46 ]. Mammary tissues were sampled from the cows at the end of the experimental period by biopsies of the upper one-third of the posterior area of one udder, using the method developed by Farr et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations